The Influence Of Brand Experience Dimensions On Brand Loyalty Of Coffee X With Age Moderation - Adji, Fine Isnadia; Sabar, Sabar (Journal Research of Social Science, Economics, and Management, 2025)
The growth of the local coffee industry in Indonesia as triggered intense competition. The ‘ngopi’ (coffee-drinking) culture, increasing purchasing power, and evolving lifestyles have created promising business opportunities. The homogeneity concepts among coffee businesses has driven the innovation of competitive advantages. Customer loyalty is crucial for sustainability of Kopi X. This research investigates the influence of brand experience on customer loyalty in local coffee shops, using Kopi X as a case study. This quantitative study employs an online questionnaire and structural equation modelling (SEM) with the aid of AMOS software. The independent variables are brand experience (sensory, affective, behavioral, and intellectual) and brand love. The dependent variable is brand loyalty, with age serving as a moderating variable. The research findings indicate that brand experience dimensions such as sensory experience, affective experience, and intellectual experience have a positive and significant effect on brand love. However, the behavioral experience dimension does not significantly influence brand love. Brand love exerts a positive and significant influence on brand loyalty. Age strengthens the influence on brand love on brand loyalty. This research is expected to provide empirical contributions to the understanding of the factors influencing loyalty in local coffee shops. The results can offer strategic recommendations for coffee business stakeholders to enhance customer loyalty through effective brand experience management.